FILOSOFI BARONG DAN RELEVANSINYA TERHADAP GENERASI MUDA DI BALI - Kadek Ari Setia Utama Putra; Kadek Ari Anggarini; Putu Pande Pinandia Eka Putri; Ni Komang Sutriyanti (UHN IGB Sugriwa Denpasar, 2021)
Bali Island is an island that is rich in culture and arts, one of which is Barong. The existence of Barong is closely related to the life of the Hindu community in Bali. Barong has a charm as a means of supporting the existence of culture and tourism in Bali. Barong's charm is expressed in the form of local Balinese products, one of which is Barong clothing in Beng Village, Gianyar District, Gianyar Regency, Bali. The Barong symbol and philosophy has strong relevance to the creativity and morale of the young generation in innovation. Indirectly, Barong has a role in reducing moral degradation that occurs among the younger generation in Bali. The objectives to be achieved in this study are to explain the Barong philosophy and its relevance to the life of the young generation in Bali and to find out how the effectiveness of the Barong philosophy in maintaining the existence of culture and its relevance to the younger generation based on SWOT analysis. Research instruments include observation, interviews, documentation, questionnaires, objects of observation, and books, and journals. The data obtained were analyzed using a qualitative descriptive method. The results of this study are as follows; It can be seen from the percentage of community responses regarding the role of Barong in every tradition in Bali of 81.00%, and the relevance of the Barong philosophy to the young generation in Bali by 92%, indicating that the Barong philosophy and the life of the community, especially the younger generation, have a continuous relationship. Based on the SWOT results, the strength of the understanding of Barong's philosophy among the younger generation is in line with the provision of understanding and development of the creativity of the younger generation. However, the development of the era of the industrial revolution 4.0 which is increasingly sophisticated is slowly causing a decline in the morale of the younger generation, so an approach is needed through interaction and provides a forum for the younger generation to channel creativity.